Effects of concentrate type and chromium propionate on insulin sensitivity, productive and reproductive parameters of lactating dairy cows consuming excessive energy - Leiva, T. [UNESP]; Cooke, R. F.; Brandao, A. P. [UNESP]; Pardelli, U. [UNESP]; Rodrigues, R. O. [UNESP]; Corra, F. N. [UNESP]; Vasconcelos, J. L. M. [UNESP] (Cambridge Univ Press, 2017)
This experiment compared insulin sensitivity parameters, milk production and reproductive outcomes in lactating dairy cows consuming excessive energy, and receiving in a 2x2 factorial arrangement design: (1) concentrate based on ground corn (CRN; n=13) or citrus pulp (PLP; n=13), and (2) supplemented (n=14) or not (n=12) with 2.5 g/day of chromium (Cr)-propionate. During the experiment (day 0 to 182), 26 multiparous, non-pregnant, lactating GirxHolstein cows (initial days in milk=80 +/- 2) were offered corn silage for ad libitum consumption, and individually received concentrate formulated to allow diets to provide 160% of their daily requirements of net energy for lactation. Cow BW and body condition score (BCS) were recorded weekly. Milk production was recorded daily and milk samples collected weekly. Blood samples were collected weekly before the morning concentrate feeding. Glucose tolerance tests (GTT; 0.5 g of glucose/kg of BW) were performed on days -3, 60, 120 and 180. Follicle aspiration for in vitro embryo production was performed via transvaginal ovum pick-up on days -1, 82 and 162. No treatment differences were detected (P >= 0.25) for BW and BCS change during the experiment. Within weekly blood samples, concentrations of serum insulin and glucose, as well as insulin : glucose ratio were similar among treatments (P >= 0.19), whereas CRN had less (P < 0.01) non-esterified fatty acid concentrations compared with PLP (0.177 v. 0.215 mmol/l; SEM=0.009). During the GTT, no treatment differences were detected (P >= 0.16) for serum glucose concentration, glucose clearance rate, glucose half-life and insulin : glucose ratio. Serum insulin concentrations were less (P=0.04) in CRN supplemented with Cr-propionate compared with non-supplemented CRN (8.2 v. 13.5 mu IU/ml, respectively; SEM=1.7), whereas Cr-propionate supplementation did not impact (P=0.70) serum insulin within PLP cows. Milk production, milk fat and solid concentrations were similar (P >= 0.48) between treatments. However, CRN had greater (P < 0.01) milk protein concentration compared with PLP (3.54% v. 3.14%, respectively; SEM=0.08). No treatment differences were detected (P >= 0.35) on number of viable oocytes collected and embryos produced within each aspiration. In summary, feeding a citrus pulp-based concentrate to lactating dairy cows consuming excessive energy did not improve insulin sensitivity, milk production and reproductive outcomes, whereas Cr-propionate supplementation only enhanced insulin sensitivity in cows receiving a corn-based concentrate during a GTT.
Keywords: chromium; concentrate type; dairy cows; energy intake; insulin sensitivity